Tales and Stories - Shelley, Mary (Saga Egmont, 2022)
Tales and Stories (1891) is a collection of short fiction by Mary Shelley. Despite her reputation as one of the foremost English novelists of the nineteenth century, Shelley also wrote numerous stories for magazines and other publications, earning a reputation as a gifted storyteller in all forms of fiction.   In “The Sisters of Albano,” a traveler resting on the banks of an Italian lake strikes up a conversation with a beautiful Countess. Inspired by the history and landscape of the region, the Countess tells the tragic story of a local family. During the French occupation of Italy under Napoleon’s rule, Anina and Maria live vastly different lives. Maria, the older sister, is a nun at the convent of Santa Chiara in Rome, while Anina, the younger, is in love with a mysterious outlaw named Domenico. When the French arrive in Albano, Anina goes searching for Domenico, who has gone into hiding with other members of the local resistance. After the young girl is arrested and sentenced to die for violating an officer’s orders, Maria, dressed in her religious habit, appeals to the French on her sister’s behalf. In “Ferdinando Eboli,” a Neapolitan Count bids farewell to his young fiancée before going off to fight for his king. When he returns, he finds that an impostor has taken over his estate—and married the unsuspecting Adalinda. With a beautifully designed cover and professionally typeset manuscript, this edition of Mary Shelley’s Tales and Stories is a classic of English literature reimagined for modern readers.